FARMERS' PREFERENCES FOR DIFFERENT FINANCIAL PRODUCT VALUES OFFERED BY COMMERCIAL BANKS IN BULGARIA - Tzvetelina Borisova (Journal of Bio-Based Marketing)
This study applies the Fishbein Model to analyze farmers' preferences for financial products offered by commercial banks. The research identifies key attributes influencing farmers' attitudes, including loan repayment period, collateral flexibility, interest rates, initial disbursement, and business consulting services. A survey was conducted among 33 farmers, utilizing a Likert scale to quantify preferences. Based on these findings, recommendations are provided for banks to improve their financial product offerings, such as extending repayment periods, increasing loan disbursement amounts, offering flexible collateral options, and enhancing advisory services. These insights help commercial banks optimize financial products tailored to agricultural sector needs.